2020
DOI: 10.3847/1538-3881/abc33d
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Polarized Thermal Emission from Directly Imaged Exoplanets and Brown Dwarf Companions to Nearby Stars

Abstract: Aerosols in the atmospheres of cloudy gas giant exoplanets and brown dwarfs scatter and polarize these objects' thermal emission. If such an object has an oblate shape or nonuniform cloud distribution, the net degree of linear polarization can show an increase ranging from several tenths of a percent to a few percent. Modern high-contrast imaging polarimeters are now poised to detect such low-polarization signals, opening up a new window into the rotational velocities and cloud properties of substellar compani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 93 publications
0
24
0
Order By: Relevance
“…Because interstellar dust creates the same polarization for the companion and the star, this contribution can often be determined from the measured stellar polarization (e.g., for 1RXS J1609, see Sect. 5.3, and ROXs 42B, see Jensen-Clem et al 2020). However, we cannot do that in this case because the star hosts a disk that we spatially resolve in our images (see Sect.…”
Section: Detection Of Intrinsic Polarization Of Dh Tau Bmentioning
confidence: 98%
“…Because interstellar dust creates the same polarization for the companion and the star, this contribution can often be determined from the measured stellar polarization (e.g., for 1RXS J1609, see Sect. 5.3, and ROXs 42B, see Jensen-Clem et al 2020). However, we cannot do that in this case because the star hosts a disk that we spatially resolve in our images (see Sect.…”
Section: Detection Of Intrinsic Polarization Of Dh Tau Bmentioning
confidence: 98%
“…In our follow-up work we will expand to multiwavelength polarization predictions, both for Luhman 16 A and B, and for brown dwarfs generally over a larger parameter phase space, given the larger data sets being accumulated (Jensen-Clem et al 2020;van Holstein et al 2021). We will also explore a wider range of GCMs for Luhman 16 A and Luhman 16 B, to assess whether the observed broadband photometric variability in the visible and near infrared, as well as the polarization signal, can be interpreted in the framework of one model.…”
Section: Discussionmentioning
confidence: 99%
“…A number of observations of polarized emission from brown dwarfs have been published as well over the past two decades (Ménard et al 2002;Manjavacas et al 2017;Zapatero Osorio et al 2005Goldman et al 2009;Tata et al 2009;Miles-Páez et al 2013;Millar-Blanchaer et al 2020). Recently, upper limits on the polarized thermal emission have been determined for a large sample (23) of exoplanets and brown dwarf companions (Jensen-Clem et al 2016;van Holstein et al 2017;Jensen-Clem et al 2020;van Holstein et al 2021;Millar-Blanchaer et al 2015) using the Gemini Planet Imager (GPI, Macintosh et al (2014)) and Spectro-Polarimetric High-contrast Exoplanet REsearch instrument (SPHERE, Beuzit et al (2019)). van Holstein et al (2021) found that polarized thermal emission measurements from DH Tau B and GSC 6214-210 B hints towards the presence of circumsubstellar disks.…”
mentioning
confidence: 99%
“…4 Using polarimetric differential imaging (PDI), the NIR polarimetric modes of the high-contrast imaging instruments SPHERE-IRDIS [7][8][9][10] at the Very Large Telescope, Germini Planetary Imager 5,11 at the Gemini South Telescope, and HiCIAO 12 at the Subaru telescope have been able to successfully image circumstellar disk of various ages. [13][14][15][16][17] SPHERE-IRDIS and the Gemini Planet imager have also been used to search for polarization signals from substellar and planetary objects, [18][19][20][21][22] leading to the polarimetric detections of two spatially unresolved circumsubstellar disks. 22 In 2017, the HiCIAO instrument at the Subaru telescope was decommissioned and replaced with the Subaru Coronagraphic Extreme Adaptive Optics (SCExAO) system.…”
Section: Introductionmentioning
confidence: 99%